Bimbingan sebaya sebagai upaya pencegahan penyalahgunaan narkoba dan perilaku romantis beresiko pada kelompok remaja - Kadek Suranata (Indonesian Institute For Counseling, Education and Therapy, 2022)
This peer group guidance program aims to increase awareness on drugs abuse and juvenile delinquency among adolescence. A group of 106 youth that members of Sekeha Truna-truni Tangkas Kori Agung, Anturan, Buleleng-Bali involved as participants of this program. This program consisted three stages namely (1) initial assessment, (2) peer guidance and mentoring webinar, and (3) final evaluation. The program evaluation carried out by measuring (1) participants activity during program, and (2) participants understanding, awareness, and commitment on drugs abuse and juvenile delinquency preventions. Results of the evaluation which were analyzed descriptively found that there was an increase in participants' understanding, awareness, and commitment not to be involved in drug abuse and juvenile delinquency such as free sex. Participants also showed enthusiasm and active involvement during the program.